ANALISIS KUALITAS PERANGKAT LUNAK LEARNING MANAGEMENT SYSTEM BERBASIS WEB DALAM MENDUKUNG SDG’S 4 (QUALITY EDUCATION) MENGGUNAKAN ISO/IEC 25010 - BAGUS, YEREZQY; Haq, Dina Zatusiva; Fitrani, Laqma Dica; Maharani, Masti Fatchiyah (Journal of Data Science Theory and Application, 2026)
Sustainable Development Goals (SDGs) Goal 4 emphasizes the importance of inclusive and equitable quality education. The utilization of information technology, particularly web-based Learning Management Systems (LMS), plays a significant role in supporting sustainable and accessible education. This study aims to analyze the software quality of a web-based LMS in supporting SDGs 4 (Quality Education) using the ISO/IEC 25010 standard. A quantitative research method with a survey approach was employed. Data were collected through questionnaires distributed to 40 LMS users consisting of students and lecturers. The software quality aspects analyzed include functional suitability, usability, reliability, and maintainability. The results indicate that the LMS demonstrates good overall software quality, with functional suitability and usability achieving very good ratings. However, reliability and maintainability aspects still require improvement to ensure long-term system sustainability. This study is expected to serve as a reference for the development and evaluation of sustainable educational software systems.